Radiation-resistant inorganic oxide flakes
Patent Information
- Application Number
- JP2022555412
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-10-06
- Filing Date
- 2021-09-30
- Publication Date
- 2025-03-06
- Estimated Expiration
- 2041-09-30
AI Technical Summary
【0016】 本発明により、耐放射線劣化性に優れる無機酸化物フレークが創出される。
Smart Images

Figure 0007641026000004 
Figure 0007641026000001 
Figure 0007641026000002
Abstract
Description
[Technical field]
[0001] The present invention relates to novel inorganic oxide flakes, and more particularly to inorganic oxide flakes having excellent resistance to radiation degradation. [Background technology]
[0002] Glass flakes are widely used as industrial materials today. For example, when glass flakes are mixed with the thermosetting resin that constitutes the lining material, the penetration of corrosive substances into the inside of the lining coating layer is suppressed, and the corrosion prevention performance of the lining material is significantly improved. For this reason, glass flakes are an essential secondary ingredient for heavy-duty corrosion-resistant lining materials. In addition, glass flakes are used as reinforcing or filling materials for thermoplastic resins, just like glass fibers. While glass fiber reinforced resins tend to have anisotropy in the mechanical strength and thermal shrinkage of molded products, glass flake reinforced resins have little anisotropy and excel in dimensional accuracy. For this reason, glass flakes are also indispensable as a secondary raw material for precision equipment materials. In recent years, glass flakes with improved chemical durability (e.g., International Patent Publication WO 2010 / 024283 A1 (Patent Document 1) and corresponding U.S. Patent Publication US 2011 / 0151261 A1 (Patent Document 2)) and glass flakes with improved chemical durability have been developed. Glass flakes with enhanced visual light absorption performance (for example, International Patent Publication WO 2004 / 076372 A1 (Patent Document 3), corresponding US Patent Publication US 2006 / 0048679 A1 (Patent Document 4)) are available according to the intended use. Glass flakes having improved properties are disclosed. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] International Patent Publication WO 2010 / 024283 A1 [Patent Document 2] US Patent Publication US 2011 / 0151261 A1 [Patent Document 3] International Patent Publication WO 2004 / 076372 A1 [Patent Document 4] US Patent Publication US 2006 / 0048679 A1 Summary of the Invention [Problem to be solved by the invention]
[0004] However, because the base material of glass flakes is glass, they have the disadvantage of deteriorating when exposed to radiation. If the radiation degradation resistance of glass flakes can be improved, they will be able to be used in facilities, equipment, parts, and components that are exposed to radiation for long periods, such as nuclear power generation facilities and space equipment, and their applications are expected to expand further. Therefore, the present inventors have attempted to develop novel inorganic oxide flakes that are excellent in resistance to radiation degradation and can replace glass flakes. [Means for solving the problem]
[0005] As a result, the present inventors have found that, in flakes made of inorganic oxides, the total content of SiO2 and Al2O3 in the flakes is in a specific range, and the ratio of Al2O3 to the total of SiO2 and Al2O3 is in a specific range. The inventors have found that flakes having excellent resistance to radiation degradation when the Fe2O3 content is within a certain range and further when the Fe2O3 and CaO contents are within specific ranges, and have completed the present invention. That is, the present invention relates to an inorganic oxide film containing SiO2, Al2O3, CaO, and Fe2O3 as main components. Lake, In the inorganic oxide flakes, calculated as oxide, i) the sum of SiO2 and Al2O3 is 40% by mass or more and 70% by mass or less, ii) The ratio (mass ratio) of Al2O3 to the total of SiO2 and Al2O3 is in the range of 0.15 to 0.40, iii) Fe2O3 is 16% by mass or more and 25% by mass or less, iv) CaO is 5% by mass or more and 30% by mass or less. The inorganic oxide flakes of the present invention have excellent resistance to radiation deterioration and are therefore suitable as a reinforcing material or filler for materials constituting a portion to be irradiated with radiation. Another aspect of the present invention provides a method for producing inorganic oxide flakes having excellent resistance to radiation degradation, using industrial waste such as fly ash, copper slag, and steel slag as raw materials. In the following explanation, the above i) to iv) may be abbreviated as "the four requirements of the present invention relating to the composition." do.
[0006] The inorganic oxide flakes of the present invention are obtained by melting a mixture of various inorganic oxides as raw materials and flaking the molten material. Here, there is no substantial difference between the component ratio of the raw material mixture (hereinafter sometimes simply referred to as the mixture) and the component ratio of the flakes obtained from the melt. Therefore, the component ratio of the raw material mixture can be regarded as the component ratio of the flakes. The inorganic oxide flakes of the present invention are characterized in that the ratio of SiO2, Al2O3, Fe2O3, and CaO in the flakes is The raw materials are blended so that the composition falls within the above range, and then the blend is melted to obtain the melt. Hereinafter, the melt of the raw material blend may be simply referred to as the melt.
[0007] The total content of SiO2 and Al2O3 in the inorganic oxide flakes of the present invention is 40 mass% or more and 70 mass% or less. % by mass or less. In the following description, SiO2 may be abbreviated as S component, and the content of SiO2 may be expressed as [S]. Similarly, Al2O3 may be abbreviated as A component, and the content of Al2O3 may be expressed as [A]. When the total of [S] and [A] is outside the above range, that is, less than 40% by mass or more than 70% by mass, the melting temperature of the blend becomes too high, or the viscosity of the melt becomes too high or too low, making it difficult to form into flakes.
[0008] In the inorganic oxide flakes of the present invention, the ratio of Al2O3 to the total of SiO2 and Al2O3 ([A] / ([A]+[S])) (mass ratio) must be in the range of 0.15 to 0.40. When the ratio of Al2O3 to the total of SiO2 and Al2O3 is either less than 0.15 or more than 0.40, it becomes difficult to melt the mixture or to form the molten product into flakes.
[0009] In the inorganic oxide flakes of the present invention, the Fe2O3 content is 16 mass% or more. If the Fe2O3 content is less than 16 mass%, the radiation deterioration resistance of the flakes is poor. On the other hand, if the content exceeds 25 mass%, the viscosity of the melt is too low, making it difficult to form the melt into flakes. Therefore, the content of Fe2O3 in the inorganic oxide flakes is set to 25 mass%. It is preferable that: Hereafter, Fe2O3 will be abbreviated as F component, and the Fe2O3 content will be expressed as [F].
[0010] In the inorganic oxide flakes of the present invention, the CaO content is 5% by mass or more and 30% by mass or less. If the CaO content is less than 5 mass %, the melting start temperature of the blend is high. This is undesirable because it increases the energy required for producing inorganic oxide flakes. The CaO content is preferably 10% by mass or more. On the other hand, if the CaO content exceeds 30% by mass, the viscosity of the melt is too low, making it difficult to form flakes. Hereinafter, CaO will be abbreviated as C component. The CaO content is sometimes expressed as [C].
[0011] In obtaining the inorganic oxide flakes of the present invention, the ratio of SiO2, Al2O3, Fe2O3, and CaO is However, there are no restrictions on the raw materials as long as they fall within the above range. Therefore, the starting materials were prepared by mixing each of the individual compounds of SiO2, Al2O3, Fe2O3, and CaO. However, it is preferable to use a mixture of a silica source rich in SiO2, an alumina source rich in Al2O3, an iron oxide source rich in Fe2O3, and a calcium oxide source rich in CaO as the starting material from the viewpoint of cost. It is preferable in this respect. Silica sources can include, but are not limited to, amorphous silica, quartz sand, fumed silica, and volcanic ash. Sources of alumina include, but are not limited to, alumina, as well as mullite and other ores. Silica-alumina sources that are rich in both silica and alumina include, but are not limited to, kaolinite, montmorillonite, feldspar, and zeolite. Sources of iron oxide include, but are not limited to, iron oxide, iron hydroxide, and iron ore. Sources of calcium oxide include, but are not limited to, calcium carbonate, as well as calcite, dolomite and other ores.
[0012] In addition to the above, waste from thermal power generation and waste from metal refining can also be effectively used as a source of silica, alumina, iron oxide, or calcium oxide. Fly ash and clinker ash can be used as the thermal power plant waste. Fly ash and clinker ash are rich in SiO2 and Al2O3, so they are called silica alumina. It is suitable as a source. However, since fly ash and clinker ash contain a small amount of Fe2O3, However, by adding an appropriate amount of iron oxide source, the inorganic oxide flakes of the present invention can be obtained at low cost. Coal gasification slag (CGS), which is produced as waste, is also used by the fly hose. Coal gasification slag has a chemical composition almost identical to that of coal ash, so it can be a source of silica-alumina. Coal gasification slag is in granular form, which makes it easy to handle. Examples of the metal refining waste mentioned above include steel slag and copper slag. Steel slag has a high CaO content and can be used as a source of calcium oxide. Includes blast furnace slag, converter slag, and reducing slag. Copper slag can be used as a source of iron oxide due to its high Fe2O3 content. Therefore, fly ash, clinker ash, or coal gasification slag can be used as the silica-alumina source, copper slag can be used as the iron oxide source, and steel slag can be used as the calcium oxide source, as appropriate. In a preferred embodiment, most of the silica alumina source, the iron oxide source, and the calcium oxide source can be supplied from industrial waste such as waste from thermal power generation and waste from metal refining. In addition, volcanic rocks such as basalt and andesite can also be used as a silica-alumina source.
[0013] The inorganic oxide flakes of the present invention do not exclude the inclusion of unavoidable impurities contained in the raw materials, such as MgO, Na2O, K2O, TiO2, and CrO2.
[0014] Since the inorganic oxide flakes of the present invention are highly amorphous, there is almost no decrease in strength due to peeling at the crystalline phase / amorphous phase interface, and inorganic oxide flakes with high strength can be obtained. Here, the degree of amorphousness, which is a measure of amorphousness, is calculated from an X-ray diffraction (XRD) spectrum by the following formula (1). Amorphousness (%)=[Ia / (Ic+Ia)]×100 (1) (In formula (1), Ic is the crystalline peak when the inorganic material is subjected to X-ray diffraction analysis. Ia is the sum of the integrals of the scattering intensities of the amorphous halo.) The degree of amorphization of the inorganic oxide flakes of the present invention, although it depends on the composition, is usually 90% or more. The degree of amorphization can reach 95% or more in high cases, and in the highest case, the flakes are essentially composed of only the amorphous phase. Here, "essentially composed of only the amorphous phase" means that only an amorphous halo is observed in the X-ray diffraction spectrum, and no peaks of the crystalline phase are observed. This means.
[0015] The resistance of the inorganic oxide flakes of the present invention to deterioration due to radiation can be known by comparing the Vickers hardness of the inorganic oxide flakes before and after exposure to radiation. Effect of the Invention
[0016] The present invention provides inorganic oxide flakes that are highly resistant to radiation degradation. [Brief description of the drawings]
[0017] [Figure 1] FIG. 1 is a diagram showing an outline of a flaking test. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0018] The present invention will be specifically described below with reference to test examples. In the following test examples (Examples and Comparative Examples), the following are used as a silica source, an alumina source, a silica-alumina source, an iron oxide source, and a calcium oxide source. <Silica source> Silicon dioxide: Reagent (hereinafter, may be referred to as SiO2 (reagent)) <Alumina source> Aluminum oxide: Reagent (hereinafter, may be referred to as Al2O3 (reagent)) <Silica-alumina source> Fly ash RM1: Fly ash containing, by mass percentage, Fe2O3: 9%, SiO2: 62%, Al2O3: 18%, and CaO: 3% <Iron oxide source> Iron(III) oxide: Reagent (hereinafter, sometimes referred to as Fe2O3(reagent)) Copper slag RM2: Copper slag containing, by mass percentage, Fe2O3: 9%, SiO2: 62%, Al2O3: 18%, and CaO: 3% <Calcium oxide source> Calcium oxide: Reagent (hereinafter, may be referred to as CaO (reagent)) Iron and steel slag RM3: by mass percentage: Fe2O3: 1%, SiO2: 19%, Al2O3: 17%, CaO: 55% Iron and steel slag containing The components of the copper slag, steel slag, and fly ash were analyzed by X-ray fluorescence analysis. Based on.
[0019] <Preparation of powdered raw materials> In the following test examples, the silica source, alumina source, iron oxide source, and calcium oxide source are each finely ground, and SiO2, Al2O3, Fe2O3, and CaO are mixed in predetermined ratios for testing.
[0020] <Flake formation test> The compound is subjected to a flaking test (evaluation of flake processability) according to the following procedure, the outline of which is shown in Figure 1. The following procedure, steps 1 through 4, is followed to melt the formulation and attempt to flake the melt. Step 1: About 60 grams of the inorganic oxide mixture (fp) that will be used to make the flakes is placed in a crucible (1) with a diameter (D1) of 20 mm. A Tammann tube (2) with a diameter (D2) of 10 mm is prepared separately. The Tammann tube (2) has an opening (21) with a diameter (Φ) of 2 mm at the bottom (Figure 1, upper part). Step 2: The crucible (1) containing the compound (fp) is heated in an electric furnace (3) (Figure 1, center left). The electric furnace is heated according to a specified heating program. The maximum temperature inside the furnace is set to 1350°C. It has been confirmed in advance that the temperature inside the crucible (1) and the molten material (fm) will follow a temperature approximately 50°C lower than the temperature inside the furnace. Step 3: After the temperature rises, the crucible (1) is immediately removed from the electric furnace (3), and the Tammann tube (2) is pushed downward from the top of the crucible (1). The inorganic oxide melt (fm) in the crucible (1) is opened. It enters the inside of the Tammann tube (2) through the mouth (21) (middle right of Figure 1). Step 4: Next, air is blown in at a pressure of about 10 MPa from the mouth (22) of the Tammann tube (2) storing the molten material (fm) (lower left in Figure 1). When the molten material (fm) has an appropriate viscosity, it expands and forms a hollow thin film balloon (fb) (lower right in Figure 1). The balloon is crushed to obtain flakes. Based on the results of the flaking test according to the above procedure, the flake processability is ranked as follows: A, B, or C. <Evaluation of flake processability> A: A balloon is formed through steps 1 to 4. B: Although the process proceeds from step 1 to step 3, a balloon is not formed in step 4 due to the low viscosity of the melt. C: Melting of the blend (fp) does not start even when step 2 is reached, or the viscosity of the molten material is high, so that the molten material does not enter the inside of the Tammann tube (2) through the opening (21) in step 3.
[0021] [Preliminary test] Prior to the series of tests, the following preliminary tests were performed. After mixing the silica source, alumina source, iron oxide source, and calcium oxide source appropriately, four samples with different SiO2, Al2O3, Fe2O3, and CaO contents were prepared and melted and solidified. Samples 3 and 4 were Although the above-mentioned requirements of the present invention are met, Samples 1 and 2 have a difference in Fe2O3 content. The abovementioned item does not meet requirement iii) of the above (Table 1). A radiation irradiation test was carried out on the obtained molten solidified sample under the condition of a gamma ray dose of 50 kGy using cobalt 60 as a radiation source, and the micro Vickers hardness was measured before and after irradiation to determine the strength retention rate of the sample after irradiation. The results are shown in Table 1. The results show that when the iron oxide (Fe2O3) content in the sample is 15% or more, the release This strongly indicates that the strength retention rate after irradiation is significantly increased.
[0022] [Table 1]
[0023] [Example 1] Fly ash RM1 is mixed with SiO2 (reagent), Al2O3 (reagent), Fe2O3 (reagent), CaO (reagent) The contents of SiO2, Al2O3, Fe2O3, and CaO in the mixture are expressed in terms of oxides. In this case, [S]+[A] is 42% by mass, [A] / ([S]+[A]): 0.20, [F] is 19% by mass, and [C] is 17% by mass. As a result of the flaking test, a balloon with a film thickness of about 800 nm was obtained. The balloon was crushed to obtain flakes. Analysis of the X-ray diffraction (XRD) spectrum revealed that the flakes were substantially amorphous. The flake samples were then irradiated with a dose of 100GGy using an electron beam as the radiation source. The Vickers hardness of the flake samples before and after radiation exposure was measured and the strength retention rate after radiation exposure was calculated in accordance with JIS Z 2244. As a result, the strength retention rate of the flakes after radiation exposure was 90%, indicating excellent resistance to radiation degradation (Table 2).
[0024] [Examples 2 to 8] By changing the amount of SiO2 (reagent), Al2O3 (reagent), Fe2O3 (reagent), and CaO (reagent) The raw material mixture was prepared by changing the total of SiO2 and Al2O3 (mass%), the ratio of Al2O3 to the total of SiO2 and Al2O3 (mass ratio), the amount of Fe2O3 (mass%), and the amount of CaO (mass%), calculated as oxides. Various preparations were made and a flaking test was carried out in the same manner as in Example 1 (Table 2). As a result, for all of the blends, the melt formed hollow thin film balloons similar to those in Example 1, and good flake processability was demonstrated. Furthermore, analysis of the X-ray diffraction (XRD) spectra revealed that all the flake samples were substantially amorphous. Next, each flake sample was subjected to a radiation irradiation test to determine the strength retention rate after radiation irradiation in the same manner as in Example 1. As a result, the strength retention rate was 90% or more in all cases, and the flakes were excellent in resistance to radiation degradation (Table 2).
[0025] [Table 2]
[0026] It is clear from Table 2 that flakes were obtained from all of the formulations that satisfied the "four composition-related requirements of the present invention," and all of the flakes had excellent resistance to radiation degradation.
[0027] [Comparative Examples 1 to 8] The mixture of SiO2 (reagent), Al2O3 (reagent), Fe2O3 (reagent), and CaO (reagent) was changed. The total of SiO2 and Al2O3 (mass%) calculated as SiO2 and Al2O3, and the percentage of Al2O3 in the total of SiO2 and Al2O3 The ratio (mass ratio), the amount of Fe2O3 (mass %), and the amount of CaO (mass %) were changed to prepare raw material blends, and tests similar to those in Example 1 were performed. The results are shown in Table 3.
[0028] [Table 3]
[0029] From Table 3, it is clear that if any one of the "four compositional requirements of the present invention" is missing, it is difficult to form the flakes, or the obtained flakes have poor resistance to radiation degradation. That is, if the value of [S]+[A] is below the lower limit of requirement i), the viscosity of the melt is too low, making it impossible to form flakes (Comparative Example 1).On the other hand, if the value of [S]+[A] is above the upper limit of requirement i), the viscosity of the melt is too high, making it difficult to form flakes (Comparative Example 2). If the value of [A] / ([S]+[A]) is less than the lower limit of requirement ii), the viscosity of the melt is too low. As a result, flakes cannot be formed (Comparative Example 3). When the value of [A] / ([S]+[A]) exceeds the upper limit of requirement ii), the viscosity of the melt is too high, making it difficult to form flakes (Comparative Example 4). Example 4). When the value of [F] is below the lower limit of requirement iii), the radiation degradation resistance is poor (Comparative Example 5). The strength retention rate after radiation exposure of the sample of Comparative Example 5 is 60%. Above the upper limit, the viscosity of the melt is too low, so that flakes cannot be formed (Comparative Example 6 ). If the value of [C] is below the lower limit of requirement iv), the viscosity of the melt is too low, resulting in flakes. When the value of [C] exceeds the upper limit of requirement iv), the viscosity of the melt becomes high. Because it is too hot, flakes cannot be formed (Comparative Example 8).
[0030] [Example 9] In this example, an example of the production of inorganic oxide flakes having excellent resistance to radiation degradation using fly ash, copper slag, and steel slag, which are industrial wastes, as raw materials, is shown. 50 parts by mass of fly ash RM1 was used as a silica-alumina source, 30 parts by mass of copper slag RM2 was used as an iron oxide source, and 20 parts by mass of steel slag RM3 was used as a calcium oxide source. The contents of SiO2, Al2O3, Fe2O3, and CaO in the mixture were calculated as [S] + [A] in terms of oxides. : 59 mass%, [A] / ([S]+[A]): 0.23, [F]: 21 mass%, [C]: 13 mass%. This raw material blend was subjected to the same tests as in Example 1. As a result, the flake processability was ranked A, and the strength retention rate after irradiation was 87%. [Industrial Applicability]
[0031] The inorganic oxide flakes of the present invention are suitable as a reinforcing material or filler for resins and rubbers. Examples of resins include thermoplastic resins and thermosetting resins. Examples of thermoplastic resins include polypropylene, ABS resin, AS resin, polyphenylene ether, polyamide, polyamideimide, Rubbers include, but are not limited to, thermoplastic rubbers. The inorganic oxide flakes of the present invention can also be suitably used as a secondary raw material for improving the corrosion resistance of lining materials and paints. The base materials for lining materials and paints include, but are not limited to, thermosetting resins such as vinyl ester resins and epoxy resins, and curable rubbers. The resin, rubber, or coating material containing the inorganic oxide flakes of the present invention has excellent resistance to radiation deterioration. Therefore, it is suitable as a material for composing a radiation-exposed part. Representative examples of radiation-exposed parts include facilities, equipment, and components in the fields of atomic energy, aerospace, and medicine. As equipment, devices and materials for the nuclear power industry, Nuclear power generation facilities, equipment and materials, Uranium ore mining and processing equipment, machinery and parts - Facilities, equipment and materials for secondary processing of nuclear fuel (including conversion, enrichment, reconversion, processing and MOX production of nuclear fuel); Facilities, equipment and materials for storing, processing and reprocessing spent nuclear fuel; Facilities, equipment and materials for storing, processing and disposing of radioactive waste; -Uranium ore, secondary nuclear fuel products, spent nuclear fuel, or radioactive waste transport equipment and components; -Other nuclear-related facilities, equipment and components. More specific examples of the facilities, equipment, and components for nuclear power generation include reactor buildings (including research reactors and test reactors), reactor containment vessels, piping within reactor facilities, and decommissioning robots. As equipment, devices and materials for the aerospace industry, Space base buildings, space stations, artificial satellites, planetary exploration satellites, space suits, etc. Equipment, devices and materials for the medical field include: - Medical devices using particle beams. The above examples of use are presented for the purpose of illustrating the usefulness of the inorganic oxide flakes of the present invention, and are not intended to limit the scope of the present invention. [Explanation of symbols]
[0032] 1 crucible 2. Tamman tube 21 Opening 22 Mouth 3. Electric furnace D1 Diameter of crucible H1 Height of crucible D2 Diameter of the Tamman tube H2 Height of Tamman tube Φ Diameter of opening fp raw material blend, inorganic oxide blend fm melt, inorganic oxide melt fb balloon P Load pressure
Claims
1. SiO 2 , Al 2 O 3 , CaO, and Fe 2 O 3 An inorganic oxide flake mainly composed of In the inorganic oxide flakes calculated as oxide, i) SiO 2 and Al 2 O 3 The total of is 40% by mass or more and 70% by mass or less, ii) Al 2 O 3 / (SiO 2 +Al 2 O 3 ) (mass ratio) is in the range of 0.15 to 0.40, iii) Fe 2 O 3 is 16% by mass or more and 25% by mass or less, iv) Inorganic oxide flakes for use in a radiation-exposed area, the CaO content being 5% by mass or more and 30% by mass or less.
2. A composition comprising a thermoplastic resin or a thermoplastic rubber and the inorganic oxide flakes of claim 1 blended therein.
3. A composition comprising a thermosetting resin or a curable rubber and the inorganic oxide flakes of claim 1 blended therewith.
4. A lining material comprising the composition according to claim 3.
5. 1. A method for producing inorganic oxide flakes, comprising melting a mixture of a silica source, an alumina source, a calcium oxide source, and an iron oxide source, comprising: In the mixture, calculated as oxide, i) SiO 2 and Al 2 O 3 The total of is 40% by mass or more and 70% by mass or less, ii) Al 2 O 3 / (SiO 2 +Al 2 O 3 ) (mass ratio) is in the range of 0.15 to 0.40, iii) Fe2O3 is 16% by mass or more and 25% by mass or less; iv) A method for producing inorganic oxide flakes for use in a radiation-irradiated portion, wherein CaO is 5% by mass or more and 30% by mass or less.
6. The method for producing inorganic oxide flakes according to claim 5, wherein the silica source or the alumina source is fly ash.
7. 6. The method of claim 5, wherein the source of iron oxide is copper slag.
8. The method for producing inorganic oxide flakes according to claim 5, wherein the calcium oxide source is steel slag.
9. 6. The method for producing inorganic oxide flakes according to claim 5, wherein the silica source or the alumina source is basalt or andesite.
10. SiO 2 , Al 2 O 3 , CaO, and Fe 2 O 3 Use of inorganic oxide flakes containing the above as a component in a radiation-exposed area, In the inorganic oxide flakes calculated as oxide, i) SiO 2 and Al 2 O 3 The total of is 40% by mass or more and 70% by mass or less, ii) Al 2 O 3 / (SiO 2 +Al 2 O 3 ) (mass ratio) is in the range of 0.15 to 0.40, iii) Fe 2 O 3 is 16% by mass or more and 25% by mass or less, iv) Use of inorganic oxide flakes containing 5% by mass or more and 30% by mass or less of CaO in a radiation-exposed area.
11. The radiation irradiated portion is a) Reactor building, reactor containment vessel, piping within reactor facilities, decommissioning robots b) Space base buildings, space stations, artificial satellites, planetary exploration satellites, space suits c) a medical device using particle beams.
Citation Information
Patent Citations
Alkali-resistant glass, manufacture, composition and reinforced cement using same
JP1985231440A
Vitrifying material for solidifying waste and waste-solidified glass
JP1998167754A
Radiation-resistant inorganic fiber and its manufacturing method
JP2022163187A
Flake glass and process for producing the same
US20060048679A1
Glass flake and coated glass flake
US20110151261A1